Envolvimento do receptor TRPA1 na nocicepção e neuroinflamação observada em modelos de esclerose múltipla em camundongos - Dalenogare, Diéssica Padilha (2022)
Multiple sclerosis (MS) is a demyelinating disease of the central nervous system (CNS), and neuropathic pain and headache are significant sensory alterations that are difficult to manage in these patients. In the different clinical forms of MS, pain and neuroinflammation are related to oxidative stress and the infiltration of inflammatory cells in the CNS. These oxidative stress products could activate ion channels, such as transient receptor potential ankyrin 1 (TRPA1). This study aimed to identify the role of the TRPA1 receptor in the nociception and neuroinflammation observed in experimental rodent models of MS. C57BL/6 female mice and mice with TRPA1 gene deletion were used (25-30 g). In both models, the antigen MOG35-55 (oligodendrocyte myelin glycoprotein) and the adjuvants Quil A and Complete Freund's Adjuvant (CFA) were administered for the relapsing-remitting MS (RRMS) and progressive MS (PMS) models, respectively. Nociception was measured by the von Frey test (mechanical allodynia in the paw and periorbital region) and the acetone test (cold allodynia in the paw region). The following treatments were performed: pregabalin, sumatriptan, olcegepant, TRPA1 antagonists (HC-030031 and A-967079), antioxidants (alfa-lipoic acid and apocynin), and TRPA1 antisense oligonucleotide by intragastrical or intrathecal route. The levels of endogenous TRPA1 agonists (hydrogen peroxide and 4-hydroxynonenal), and NADPH oxidase and superoxide dismutase (SOD) activity were evaluated in the spinal cord, trigeminal ganglion, and brainstem samples. Different markers of demyelination, neuroinflammation, and TRPA1 expression were also evaluated using the RNA expression technique for the EMRR mouse model. Immunohistochemistry was performed evaluating the Iba-1, GFAP, and OLIG-2 markers for the two MS models. Firstly, the induced mice to RRMS mouse model developed mechanical (hind paw and periorbital region) and cold (hind paw) allodynia. After, the administration of pregabalin, sumatriptan, olgepant, TRPA1 antagonists, antioxidants and the TRPA1 antisense oligonucleotide showed an antinociceptive effect in the EMRR mouse model. The levels of hydrogen peroxide and 4-hydroxynonenal and NADPH oxidase activity were increased in the spinal cord and trigeminal ganglion samples of RRMS induced mice. The deletion of TRPA1 channels attenuated the development of nociception in the EMRR and EMP induced mice. Genetic deletion of TRPA1 channels was also able to attenuate the increase in Iba-1 GFAP and OLIG-2 markers in the induced animals in both MS models. By Fastblue staining the TRPA1 deletion might prevent the demyelinating process. However, the TRPA1 knockout animals showed no attenuation in clinical scores after the two MS inductions. These results show the involvement of TRPA1 in nociception and neuroinflammation behaviors in these two MS models.